Oseltamivir use in infants under one year of age: are there still unanswered questions? - Kara, Ateş; Karadağ-Öncel, Eda; Özkaya-Parlakay, Aslınur; Korukluoğlu, Gülay; Bağdat, Arzu; Celik, Melda; Ceyhan, Mehmet; Cengiz, Ali Bülent (The Turkish Journal of Pediatrics, 2012)
The influenza A (H1N1) virus responsible for the 2009 pandemic follows a more severe course in children, thus increasing the need for hospitalization. On the other hand, during the first weeks of the pandemic, use of oseltamivir (Tamiflu) in children was restricted, and it was not yet approved for use in children younger than one year of age because of the lack of adequate safety and efficacy data and because of concerns regarding central nervous system (CNS) toxicity in newborn rats. However, citing a state of emergency, conditional approval was granted first in the United States, then Europe and finally in Turkey. The main aim of this study was to share our experience with oseltamivir in 35 patients less than one year of age during the 2009 H1N1 pandemic. A total of 35 infants (21 boys, 14 girls; mean age: 160 days [24-335]) were treated during the study period. Six patients required hospitalization, five of whom (14.2%) had an underlying chronic disorder. During the pandemic, we diagnosed H1N1 infection based on clinical symptoms. Nasal swabs were positive for H1N1 in 88.5% of cases. Mild elevations in liver enzymes were present in 39.1% of patients with available blood workup at presentation, and no changes in liver enzymes were observed with oseltamivir treatment. None of the patients developed any neurological, dermatological or gastrointestinal side effects in association with oseltamivir treatment. No complaints of drowsiness, lethargy or sleep disturbance were reported by the parents. Although our case number is very limited, our study results suggest that oseltamivir is well tolerated in young infants, and we can conclude that oseltamivir could be used in the treatment of influenza A in this age group. Nevertheless, further studies are needed to evaluate using oseltamivir in more cases among infancy age groups.